Silent honor - Steel, Danielle (New York, N.Y. : Dell, 1997)
Eighteen-year-old Hiroko comes to California in 1941 to attend college at Berkley, but even her love for teaching assistant Peter Jenkins cannot keep her from longing for home. Sadly, her dream of returning to Japan ends with the bombing of Pearl Harbor, and Hiroko must learn to survive in her rapidly changing world.
Kirkus Review
Library Journal
Publisher's Weekly
Adult.
Adult
Keywords: Japanese Americans -- Evacuation and relocation,1942-1945 -- Fiction; Japanese Americans -- California -- Fiction; Young women -- California -- Fiction; Japanese Americans -- Fiction; World War, 1939-1945 -- United States; Young women -- Fiction; California -- Fiction; Historical fiction